(untitled) (Rural Development Journal, 2024)
This study focuses on the role of remittances in the Nepalese economy drawing on data from the different secondary data. It analyzes the influence on household income, poverty alleviation, and overall economic development. The research then presents regression analysis between remittance and HDI and finds a high correlation. While finding remittance to be critical to Nepal’s improving quality of life, the study also highlights challenges associated with remittances, including brain drain and over reliance. The article advocates for a strategic approach to continue maximizing their positive impact on the national economic landscape.